Implementation of Cloud-Based Information Systems for the Optimization of Higher Education Administration Services - Khaeruddin; Mohammad Nur Cholis; Arisandi (Ran Edu Center, 2025)
Digital transformation in the higher education sector requires increased efficiency, flexibility, and quality in the delivery of administrative services. Conventional on-premise information systems often face obstacles in terms of scalability, accessibility, and infrastructure maintenance, thereby hampering the effectiveness of academic and financial services. This study aims to design and implement a cloud computing-based information system to optimize higher education administrative services. The research method uses a software engineering-based case study approach with an iterative System Development Life Cycle (SDLC) development model, covering the stages of requirements analysis, system design, implementation, and evaluation. The system was built with a Software as a Service (SaaS) architecture using the Google Cloud platform and tested on two main service units, namely academic and financial. The test results showed an increase in administrative process time efficiency of up to 61.75%, a system uptime rate of 99.8%, and an average user satisfaction rate of 4.51 on a scale of 5. These findings indicate that the application of cloud computing can significantly improve operational efficiency, data security, and user satisfaction, while supporting the digital transformation of higher education institutions towards adaptive, integrated, and sustainable administrative governance.